Organizational Tenure and Job Performance - Ng, Thomas W. H.; Feldman, Daniel C. (Journal of Management, 2010)
This study provides a meta-analysis on the relationships between organizational tenure and three broad classes of job behaviors: core-task behaviors, citizenship behaviors, and counterproductive behaviors. Across 350 empirical studies with a cumulative sample size of 249,841, the authors found that longer tenured employees generally have greater in-role performance and citizenship performance. It is interesting that organizational tenure was also positively related to some counterproductive behaviors (e.g., aggressive behavior and nonsickness absence). Most of these relationships remain statistically significant even after controlling for the effects of chronological age. The authors also observed that the tenure—performance relationship was stronger for younger workers, for women, for non-Caucasians, and for college-educated workers. Finally, the authors found evidence of a curvilinear relationship between organizational tenure and job performance. Although the relationship of organizational tenure with job performance is positive in general, the strength of the association decreases as organizational tenure increases.